Slip of the Tongue in English-Language Debates: A Psycholinguistic Study - Sariasih, Wiwit; Rafli, Zainal; Boeriswati, Endry (KnE Social Sciences, 2023)
Debaters need to plan, speak fluently, and think critically during a debate. However, a common error occurs during debates known as slips of the tongue. They are caused by nervousness, tension and unpreparedness. This research aimed to identify types of slips of the tongue and their units of error through a descriptive qualitative study. The data were collected from the video recording of an English Debate Competition at a university. The data were analyzed using two theories by Gleason and Ratner Click or tap here to enter text.and by DardjowidjojoClick or tap here to enter text. to investigate units of error in slips of the tongue. The second theory was presented by Altiparmak and Koruoglu which described nine types of slips of the tongue: shifts, exchanges, anticipations, persistence, additions, deletions, substitutions, blends, and deviations. There were 78 data points found in slips of the tongue - 39 units of error and 39 types of error. The units of error found in slips of the tongue were 11 distinctive feature errors, 9 syllable errors, 6 phonetic segment errors and 14 word errors. Types of the slips of the tongue were 15 deletions, 9 substitutions, 11 blends, and 4 deviations. Keywords: Debate, Slips of Tongue, Unit of Error